Towards an indicator of copper emissions from ships in Swedish waters - A case study on two ships types operating in Swedish waters - Nordqvist, John; Sjöberg, Martin (My University, 2021)
The Swedish Cross-Party Committee on Environmental Objectives has proposed Traffic analysis to follow up and evaluate the impact from shipping on the marine environment. Today there are only few indicators in use, and only for air emissions. This study has focused on copper emissions as an indicator and what sources on the ship that releases copper. The Kongsberg engine simulator has been used to simulate two different types of ships, ferry and a very large crude carrier (VLCC). To determine the volume of water that the different sources produce. The result from the two ships can be the starting point in further research and development of indicators related to water emission. That can give more understanding of the impact on the marine environment caused by the shipping industry.